11.6k views
4 votes
What is the simplified form of the following expression 2sqrt27 + sqrt12-3sqrt3-2sqrt12

What is the simplified form of the following expression 2sqrt27 + sqrt12-3sqrt3-2sqrt-example-1
User Wim Leers
by
5.6k points

2 Answers

2 votes

Answer:

AAAAAAAAAAAAAAAA

Explanation:

User Linktoahref
by
6.0k points
5 votes

Answer:

√3

Explanation:

Given:


2√(27)+√(12)-3√(3)-2√(12)\\=2√(27)-√(12)-3√(3)\\

Writing √12 =2√3 and 2√27=6√3

Now
=6√(3)-2√(3)-3√(3)\\=√(3) !

User Nathan Wilson
by
5.6k points